Exploring the Pathways to Engagement: The Role of Psychological Climate, Gratitude, and Self-Efficacy in Small Business Contexts - Putranta, Martinus Parnawa (KINERJA, 2025)
This study explores the relationship between psychological climate and work engagement, focusing on the mediating roles of gratitude and general self-efficacy in small business contexts. Data were collected from 180 employees working in small businesses in two cities in Central Java through an online questionnaire. Respondents were selected using a purposive sampling technique to ensure relevant work experience. Structural Equation Modeling (SEM) with Partial Least Squares (PLS) was employed to analyze the data. The results revealed that the direct influence of psychological climate on work engagement was not supported. However, the findings underscore the significant mediating roles of gratitude and general self-efficacy. Gratitude amplifies emotional connection, while general self-efficacy fosters confidence translating a positive psychological climate into greater work engagement. These findings highlight the importance of internal psychological mechanisms in driving employee engagement in small businesses. The study suggests that managers should focus on creating a supportive workplace climate while fostering gratitude and self-efficacy through targeted interventions. These strategies could help small businesses enhance employee engagement, even in resource-constrained environments. Future research could explore additional mediators and longitudinal effects to deepen the understanding of these relationships.